Adsorción de Cadmio, Cobre y Plomo en Bentonita, Caolín y Zeolita Naturales y Modificadas: Una Revisión de los Parámetros de Operación, Isotermas y Cinética - Carbonel, Dalia (Ingeniería, 2018)
Context: Adsorption is a tertiary wastewater treatment that can be effectively employed to remove metal ions from aqueous solutions. Natural and modified clays and zeolites have been widely use as low-cost materials to increase the competitive advantage of the process. Methodology: A comprehensive review was made amongst articles, that during the last decade, have studied cadmium, copper and lead adsorption onto natural and modified bentonite, clay and zeolite. Results: Different process parameters, equilibrium conditions and kinetics were analyzed. Operation parameters studied were initial metal ion concentration, solution pH, adsorbent dosage and temperature. Compilation of system efficiencies, in regards to maximum adsorption capacity, is presented. Isotherm models to assess adsorption equilibrium as well as kinetic and diffusion models in studies reviewed are discussed. Conclusions: Bentonite, kaolin and zeolite have been proven to be adequate materials to remove cadmium, copper and lead from aqueous solutions. The different adsorption capacities of cadmium, lead and copper are a reflection of the influence of many process parameters. The Langmuir isotherm usually describes best the equilibrium adsorption in the articles reviewed. Finally, the pseudo-second orden model better describes the kinetics in many cases.